ANALISIS TINGKAT NON-REVENUE WATER (NRW) PADA JARINGAN DISTRIBUSI SPAM PUSAT PERUMDA AIR MINUM PALANGKA RAYA - Nanda, Fahreza Alvian; Masduqi, Ali; Ahyar, Agus; Adhi, Bagas Wahyu (Jurnal Teknik Sipil Giratory UPGRIS, 2024)
NRW is still a problem for PDAMs in Indonesia in providing drinking water for the community. This can be seen from the national average NRW level in 2021, which was 33.72% (higher than the RPJMN target of 30%). The ATR reduction strategy can be carried out correctly if the indicators or components are accurately measured. The problem is that many PDAMs need help to understand the definition or calculate ATR components according to international standards with high confidence. In this research, a water balance was prepared using WB-EasyCalc to determine the value of each ATR component with a 95% confidence level, potential loss of income, and ILI value. The results of the water balance analysis show that the ATR level at Perumda Air Minum Palangka Raya in May 2023 was 51.84%. This percentage comprises 2.19% non-revenue official consumption and 49.64% water loss. If the NRW percentage is not reduced, the potential loss of income is estimated at IDR 15,395,984,969/year. The component that causes the most water loss is physical water loss, which reaches 42.67%. The physical water loss performance indicator (ILI) has a value of 23, which is included in performance category D (extraordinary waste of resources occurs, and leak reduction programs must be prioritized). Recommendations that can be given are related to the active leak detection and pressure management.